Characteristic Features of the Movement of Elastic-Viscoplastic Flu-id in Pipelines and Formations - Dadash zade, Kh.I.; Makhmudova, V.Z. (Herald of Azerbaijan Engineering Academy, 2025)
Numerous tasks of field practice are largely dependent on the physical properties of hydrocarbons, which include oil. The presence of paraffin, asphaltene and resins in oil has a significant impact on the movement regime, and, consequently, on the design of technological processes for drilling, well operation, field development and pipeline transport of oil. In many fields around the world, the process of pressure recovery when determining reservoir pressure lasts a very long time, in some cases several weeks or months, which is explained by the manifestation of nonequilibrium effects, i.e. elastic properties of liquid. Laboratory experiments have proven that if paraffins, asphaltenes and resins exist in the oil, then they give such oils viscoelastic properties, i.e., along with viscous properties, they also have elastic properties. These oils are considered from the perspective of nonequilibrium liquids, i.e., the rate of change in their internal structure is significantly lower than the rate of change in external conditions. To describe the be-havior of visco-plastic-elastic properties, we propose a model taking into account the relaxing properties of the system.